The effect of ZnSe Core/shell on the properties of the window layer of the solar cell and its applications in solar energy. (November 2020) - Abdalameer, Nisreen Kh.; Mazhir, Sabah N.; Aadim, Kadhim A.
Abstract: In this paper, ZnSe nanoparticles (ZnSe NPs) were prepared by selenium nitrate and zinc metal sheets to improve the absorption coefficient that affects the solar cell. Also, core–shell structured ZnSe was prepared by atmospheric pressure plasma jet system. The structure properties and optical were described by X-ray (XRD) diffraction, and ZnSe NP absorbance measurements. Finally, with support from structural and optical studies, the current density–voltage (J–V) properties of n-ZnSe/p-Si solar films found that conversion efficiency strongly depends on strongly porous silicone time. fill factor (F.F) increase from (0.40 to 0.56) with increasing porous time andefficiency ( η ) increasing from 0.89 to 2 with increase porous time from 5min to 20 min.